Penggunaan Sertifikat Elektronik untuk Meningkatkan Efisiensi Pendaftaran Tanah dalam Upaya Pencegahan Mafia Tanah - Raden Ayu Rani Mutiara Dewi; Catherine Susantio (Jurnal Syntax Admiration, 2024)
Uneven and unintegrated land administration, along with numerous uncertified land plots in Indonesia, are contributing factors to the emergence of land mafias. Land mafia is a form of land crime involving a group or individual illegally obtaining or controlling others' land, against the law. The implementation of Electronic Certificates (E-Certificates) is seen as a solution to mitigate the widespread challenges posed by land mafia practices. This study aims to analyze these issues and explore effective methods for implementing E-Certificates in land registration processes. The research employs a juridical normative method or legal literature research (library research). E-Certificates enable more efficient and secure use of electronic documents, simplifying the overall land registration process. The study also discusses Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency of the Republic of Indonesia Number 3 of 2023 concerning the Issuance of Electronic Documents in Land Registration Activities, which sets crucial requirements for E-Certificates. Thus, this research asserts that the introduction of Electronic Certificates is expected to effectively enhance land registration efficiency and reduce land mafia practices in Indonesia.